The Impact of Non-Formal Entrepreneurship Education on Entrepreneurial Motivation among PKBM Learners in Banyuwangi: Exploring Entrepreneurial Attitude as a Mediating Variable - Dian Mulyasari; F. Danardana Murwani; Ludi Wishnu Wardana (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research about Community Learning Activity Centers (PKBM) in Banyuwangi emerge as pivotal entities, crucial for elevating the quality of non-formal learning and providing support to learners during the crisis. Focused on mitigating the substantial repercussions of the Covid-19 pandemic on education and the economy, the strategy employed centers on enhancing the quality of non-formal education in PKBM to harness the community's potential. The research's urgency is underscored by the potential to enhance skills and competencies among PKBM beneficiaries, particularly in the entrepreneurial sphere. Findings underscore that Non-Formal Entrepreneurship Education significantly and positively influences Entrepreneurial Motivation, both directly and mediated by Entrepreneurial Attitude.